Feeding Poultry for Special Purpose: Omega-3 Polyunsaturated Fatty Acid Table Eggs as Functional Food: A Review Article - Elsedeg, Somaia (Journal of agricultural, environmental and veterinary sciences, 2017)
At the beginning of the twenty- first century, the science of human nutrition has been considered as a way for improving life quality and wellness. The role of food in human health and the awareness of consumers for healthy food directed research towards the production of food that has specific health effects on disease prevention and treatment. These foods are satisfactorily demonstrated to affect beneficially one or more target functions in the body, beyond adequate nutrition. These foods are termed functional foods. Production of omega-3 table eggs as functional food is a new paradigm in poultry for. The ability of monogastric animals to deposited dietary fatty acids in their tissues without significant modifications on the sensory value of these products was the foundation stone and the starting point to produce omega-3 eggs. Several research activities have been conducted to increase the level of omega-3 polyunsaturated fatty acids in poultry products. The working knowledge of current literature concerning this topic made the strong foundation to produce this type of functional foods. The dietary sources of omega-3 fatty acids used for feeding laying hens modified the fatty acid content of the egg yolk. Some sources deposited amounts of fatty acids made those eggs suitable to be served as functional food. Increasing omega-3 polyunsaturated fatty acid content of eggs could be achieved either by enrichment of the diet with alpha-linolenic rich sources such as flaxseed, linseed or by EPA and DHA rich fish oil and fish meal.